1998
DOI: 10.1162/089892998562816
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Complex Visual Perception Following Unilateral Temporal Lobectomy

Abstract: Although human temporal cortex is known to be important for short- and long-term memory, its role in visual perception is not well understood. In this study, we compared the performance of three patients with unilateral temporal lobectomies to that of normal controls on both "simple" and "complex" visual discriminations that did not involve explicit memory components. Two types of complex tasks were tested that involved discriminations secondary to texture segmentation. These were contrasted with simple discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…These very limited effects of the lesions on acuity are in agreement with other studies in which basic visual capabilities were found to be intact after mid‐level and high‐level extrastriate lesions (e.g. Merigan, 1996; Huxlin & Merigan, 1998). In addition, a previous study with the same two monkeys (De Weerd et al ., 1999) demonstrated that grating orientation discrimination was unimpaired in lesion‐affected quadrants for contrasts as low as 2.5%.…”
Section: Assessment Of Other Perceptual Capabilitiessupporting
confidence: 92%
“…These very limited effects of the lesions on acuity are in agreement with other studies in which basic visual capabilities were found to be intact after mid‐level and high‐level extrastriate lesions (e.g. Merigan, 1996; Huxlin & Merigan, 1998). In addition, a previous study with the same two monkeys (De Weerd et al ., 1999) demonstrated that grating orientation discrimination was unimpaired in lesion‐affected quadrants for contrasts as low as 2.5%.…”
Section: Assessment Of Other Perceptual Capabilitiessupporting
confidence: 92%
“…Although evidence suggests a contralateral relationship between temporal lobe and visual field in some specific areas of the temporal lobe, higher-level temporal areas possess a representation of the entire central visual field in each of the two temporal lobes (Gross, Rocha-Miranda, & Bender, 1972). Huxlin and Merigan (1998) report that visual deficits produced by temporal lobectomy in humans are found in both ipsilateral and contralateral visual hemifields. Given that the location of the middle and inner ear is towards the underside of the temporal lobe, and the possibility that the temporal lobes are not contralaterally related to visual hemifields, it seems possible that eye preference (a self-report measure of preference for one eye over another) may also be related to TMT Diff, leading to:…”
Section: Tmt Diff and Eye Preferencementioning
confidence: 99%
“…Tympanic membrane temperature difference (TMT Diff) will be negatively correlated with eye preference However, as noted by Huxlin and Merigan (1998), the role of the human temporal cortex in vision is not well understood. As a result, the possibility of a contralateral link between eye preference and TMT Diff is relatively speculative.…”
Section: Tmt Diff and Eye Preferencementioning
confidence: 99%
“…ICs have garnered considerable interest because of their "inferential" nature-despite the lack of luminance edges, the visual system uses implicit configural cues to infer the presence of a contour. Finally, behavioral investigations in macaque suggest that IC perception is strongly dependent on higher visual areas, including V4 (37,38) and inferotemporal (IT) cortex (39,40).…”
mentioning
confidence: 99%